Di Bawah Naungan Sang Kejora:"Nasionalisme" Papua Anti Indonesia? - I Ngurah Suryawan (PAX HUMANA, 2015)
This paper discusses the thought and imagination that exist among somePapuans about what they call "Papuan nationalism". One of the symbols of"nationalism" is the Bintang Kejora Flag. Papuan People construct theirown social history which is always at odds with the effort to make thePapuans becomes Indonesian . The history of violence, suffering anddiscrimination of development in Papua had been planted into the soul ofpapuan people and that make different feelings such as anti Indonesia.This paper argues that the efforts of social movements for recognition ofhistory and identity of the Papuan people has become very important. One ofthe effort that could be done is to bring the history back which is "darkened"on Papua through the motions of writing papuans own history among thePapuans themselves.Keywords: nationalism, history, violence, social movements, identity